Pengaruh Dukungan Organisasi, Pengembangan Karir terhadap Kepuasan Kerja dan Turnover Intention pada Karyawan Operasional PT. CRS ( Siantar Top Group, Tbk ) - Hidayah, Nur; Litfiana, Rika (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2024)
The purpose of this study examine and analyze the influence of organizational support, career development on job satisfaction and turnover intention employees PT. CRS (Siantar Top Group, Tbk) Surabaya. The approach used for this research is quantitative approach. Population in this research is operational employee of PT. CRS Surabaya. The instrument used in this study is a questionnaire consisting of a number of questions about organizational support, career development, job satisfaction, and turnover intention. The number of samples used in this study amounted to 117 respondents. Data were collected personally by distributing questionnaires to a number of respondents to obtain primary data. Data analyst technique uses path analysis. Based on the research results, and the discussion that has been described, it can be concluded that 1) Organizational support has a positive and significant impact on employee job satisfaction; 2) career development has a positive and significant impact on job satisfaction; 3) Job satisfaction has a positive and significant impact on turnover intention; 4) Organizational support has a positive and significant impact on turnover itention; 5) Career development has a positive and significant impact on turnover intention